AN ANALYSIS OF REQUEST SPEECH ACT IN THE MAN FROM TORONTO MOVIE - Agustinus Deni; Christina Maya Iriana Sari (Universitas Katolik Widya Mandala Surabaya, 2023)
This study aims to analyze the strategies and functions of request speech acts used in the movie entitled The Man From Toronto. A request speech act is a directive speech act whose purpose is to instruct the listener to do something. This study used a descriptive qualitative method. All data in this study were taken from conversations between characters that contained speech acts in the form of requests and transcribed into text form. Then, the collected data is classified based on the request strategy Â and functions. Based on the results of the study, there were seven out of eight request strategies in this study. The performative request strategy was not found in this study. The seven strategies found in this research are hints (26 data), abilities/willingness/permissions (6 data), suggestory formulae (5 data), wishes (4 data), desires/needs (6 data), obligation statements (4 data), and imperatives (25 data). The most dominant strategy of request is hints strategy. Hints are needed because there are differences in social status including power and distance among the characters in the movie. The lack of use of the wishes strategy and statement of obligation is caused by the requester who prefers to use the imperative strategy where it is considered very easy and the request will be more easily understood by the listener. The four functions of request found in this research are request for information, request for action, request for goods, and request for permissions. The most dominant function is the request for action that is conducted by the characters whose social status is higher than the addressee. Â Keywords: Speech act, Request, Request Strategies, Request Functions, Movie